1998
DOI: 10.1177/0907568298005001007
|View full text |Cite
|
Sign up to set email alerts
|

Children and Citizenship in Britain

Abstract: In the 1980s and 1900s there has been a substantial amount of discussion around notions of citizenship. Given the marginal treatment of children in mainstream sociology in the 1980s, it is small wonder that no mention is made of children in these discussions. This article challenges most conceptions of citizenship as they currently stand in their exclusion of children. It adopts a social model of citizenship that emphasizes the ways in which people are connected to each other, rather than being viewed as actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(28 citation statements)
references
References 20 publications
0
26
0
2
Order By: Relevance
“…Although we are far from being a society that routinely recognizes children's and adolescents' rights to societal participation (such as contributing to decision-making about urban planning, transport provision, leisure, healthcare, etc. ), the case for children's citizenship, even if partial, has been made articulately and powerfully (Cockburn, 1998;De Winter, 1997;Held, 1991;King, 1997). Nonetheless, there is clearly a long way to go-for example, under UK legislation children lack the right even to form a pupil council!…”
Section: Social Categories Social Perception and Group Identitymentioning
confidence: 99%
“…Although we are far from being a society that routinely recognizes children's and adolescents' rights to societal participation (such as contributing to decision-making about urban planning, transport provision, leisure, healthcare, etc. ), the case for children's citizenship, even if partial, has been made articulately and powerfully (Cockburn, 1998;De Winter, 1997;Held, 1991;King, 1997). Nonetheless, there is clearly a long way to go-for example, under UK legislation children lack the right even to form a pupil council!…”
Section: Social Categories Social Perception and Group Identitymentioning
confidence: 99%
“…This is an interesting point touching on current debates about the changing nature of citizenship. Cockburn (1998), for example, states that the feminist critique of concepts of citizenship have shown that the idea of the independent individual as citizen is an ideological construct which masks the dependency of 'public man' on a network of social support provided in the 'private' sphere of the family. This, it is suggested, could also form a starting point for children's claim to a (perhaps modified) form of citizenship.…”
Section: Developments In Policymentioning
confidence: 99%
“…It seems improbable, though, that young people will be content to limit their pursuit of self-determination to the domestic sphere and it is already evident that the horizons of some young people are more expansive (Cockburn, 1998).…”
Section: Debates About Childhoodmentioning
confidence: 98%